Highlights: Bootcamp— AgriTech4Egypt Innovation Challenge - CGIAR Accelerate for Impact Platform (2024)
On 10-13 June 2024, 50 of the most innovative minds in agri-tech came together in rural Belbeis, on the outskirts of Cairo, Egypt, to connect, accelerate, and scale-up their solutions with the AgriTech4Egypt Innovation Challenge Bootcamp, powered by the CGIAR Accelerate for Impact Platform (A4IP) and supported by an international consortium of partners. Representing 25 teams from 11 nationalities and 5 CGIAR-led teams, these participants competed to move to the next stage of the challenge— the acceleration program.